2017
DOI: 10.1007/s10508-017-0950-4
|View full text |Cite
|
Sign up to set email alerts
|

“We Deserve Better!”: Perceptions of HIV Testing Campaigns Among Black and Latino MSM in New York City

Abstract: In 2014, Black/African-American and Hispanic/Latino men who have sex with men (BLMSM) comprised 64.1% of HIV diagnoses among MSM in the U.S. Routine HIV testing allows earlier diagnosis, linkage to care, and improved health outcomes. HIV testing campaigns may increase HIV awareness and testing behaviors, but perceptions of these campaigns by BLMSM have been understudied. We explored perceptions of HIV testing campaigns with BLMSM in New York City (NYC) to inform campaign strategies that target BLMSM for HIV te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…Although, it is important to note that the limited information regarding pre-testing, or on how representative GBMSM involved in this might be, means we are unable to determine the level of involvement GBMSM may have had in the creation of these images and thus how culturally specific these messages were. Drumhiller et al (2018) suggested that some intervention recipients may prefer images that are more broadly relatable, less stereotypical and not identifiable as GBMSM, to avoid stigmatising GBMSM as solely affected by HIV. As more extensive formative research is associated with a greater likelihood of impact (Stead et al, 2007), we would suggest that this should be a key part of the development process and should be clearly described when reporting on the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Although, it is important to note that the limited information regarding pre-testing, or on how representative GBMSM involved in this might be, means we are unable to determine the level of involvement GBMSM may have had in the creation of these images and thus how culturally specific these messages were. Drumhiller et al (2018) suggested that some intervention recipients may prefer images that are more broadly relatable, less stereotypical and not identifiable as GBMSM, to avoid stigmatising GBMSM as solely affected by HIV. As more extensive formative research is associated with a greater likelihood of impact (Stead et al, 2007), we would suggest that this should be a key part of the development process and should be clearly described when reporting on the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous analysis using data from this survey, Sullivan and Stephenson found that MSM perceiving a lower local community HIV prevalence were more likely to engage in higher risk sexual behavior and less likely to have a recent HIV test ( Sullivan & Stephenson, 2017 ). Perception of HIV risk, and whether or not that contributes to actual risk, varies by population and may be the result of HIV prevention and testing campaigns and interventions that may not adequately target higher risk populations ( Albarracin et al, 2005 ; Drumhiller et al., 2017 ). Strategies to improve HIV prevention messaging should be considered for increasing knowledge and appropriate perception of individual HIV risk.…”
Section: Discussionmentioning
confidence: 99%
“…Stop HIV and Get Yourself Tested). Public health campaigns have prioritized encouraging all adults to test for HIV infection and individuals with higher risk to engage in routine testing (Center for Disease Control and Prevention CDC, 2019d, 2019e; Drumhiller et al, 2018; Habarta et al, 2017). However, HIV testing rates remain low among young adults.…”
Section: Discussionmentioning
confidence: 99%
“…The successes of some of these campaigns have been difficult to estimate due to limited published research on the effectiveness and sustainability in changing attitudes or behaviors related to HIV testing (French, Bonell, Wellings, & Weatherburn, 2014; Olawepo, Pharr, & Kachen, 2019). Factors like transient campaign periods, cost and limited funding, and noninclusive messaging, hamper the effectiveness of public health HIV testing campaigns (Drumhiller et al, 2018; Garbers, Friedman, & Martinez, 2016; Roston et al, 2014). The limited ability of planned parenthood to provide HIV testing services further limits access to testing for young adults who do not have insurance or access to student health centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation